Association between interleukin-4 polymorphisms and asthma - 李亚斐 郭波涛 韩家信 朱才众 张耀 马翔宇 张路 熊鸿燕 (Journal of Medical Colleges of PLA, 2007)
Objective：To perform a systematic review and meta analysis on the association of C-589T and C-590T polymorphisms of IL-4 with asthma and to estimate allele frequencies, the magnitude of the gene effect as well as the possible mode of inheritance. Methods： A genetic model-free approach was used to perform a meta analysis. Heterogeneity, sensitivity analysis and publication bias were also explored. Results： Our meta analysis summarized the evidence to date regarding the association of C-589T and C-590T polymorphisms in the promoter region of IL-4 gene with asthma. For C-590T, the results showed a significant recessive genetic model, and the CC genotype was about 24% less likely to have asthma than the genotype CT and TT. Although there was evidence suggesting a recessive genetic model for C-589T, the recessive model was not statistically significant. Conclusion： This meta analysis suggests that there may be an important effect of single nucleotide polymorphisms （SNPs） in the promoter region of IL-4 gene on the pathogenesis of asthma.